Forms of Care: Chimamanda Ngozi Adichie’s Americanah (2014), Agency, and Decolonial Feminism - McCann, Fiona (Études littéraires africaines)

(untitled) (Association pour l'Étude des Littératures africaines (APELA), 2021)
This article explores feminist politics in Chimimanda Ngozi Adichie’s Americanah and the ways in which it interlinks with forms of care. I tease out the author’s engagement with intersectional feminism as well as her blind spots. I situate Adiche’s work within the context of postcolonial, popular and decolonial feminism, unpacking the significance of hair and the more general question of agency. I then move to show that the poetics of care developed in the novel ultimately falls short of embracing a decolonial feminist stance due to the relative invisibility of the neo-colonial structures at work in contemporary Nigeria.